Fixel-Based Analysis Effectively Identifies White Matter Tract Degeneration in Huntington’s Disease - Oh, Sher Li; Chen, Chiung-Mei; Wu, Yih-Ru; Valdes Hernandez, Maria; Tsai, Chih-Chien; Cheng, Jur-Shan; Chen, Yao-Liang; Wu, Yi-Ming; Lin, Yu-Chun; Wang, Jiun-Jie (Frontiers in Neuroscience, 2021)
Microstructure damage in white matter might be linked to regional and global atrophy in Huntington Disease. We hypothesize that degeneration of subcortical regions, including the basal ganglia, is associated with damage of white matter tracts linking these affected regions. We aim to use fixel-based analysis to identify microstructural changes in the white matter tracts. To further assess the associated grey matter damage, diffusion tensor-derived indices were measured from regions of interest located in the basal ganglia. Diffusion weighted images were acquired from 12 patients with Huntington’s Disease and 12 healthy unrelated controls using a 3 Tesla scanner. Reductions in fixel-derived metrics occurs in major white matter tracts, noticeably in corpus callosum, internal capsule and the corticospinal tract, which were closely co-localized with the regions of increased diffusivity in basal ganglia. These changes in diffusion can be attributed to potential axonal degeneration. Fixel-based analysis is effective in studying white matter tractography and fiber changes in Huntington’s Disease.